Деформации параметров динамических систем и их влияние на вычислительный процесс - Задорожный, В.Ф. (Кибернетика и системный анализ, 2009)
Розглянуто динамічні системи як математичні моделі фізичних явищ і вплив малих збурень початкових умов та їх структури на точність обчислень. Показано, що для коректності обчислювальних процесів спочатку необхідно дослідити фазовий портрет динамічної системи. Dynamic systems as mathematical models of physical phenomena and the influence of small perturbations of initial conditions and their structure on the calculation accuracy are considered. It is shown that, to provide the correctness of a computational process, the phase portrait of a dynamical system should first be studied.